2014
DOI: 10.1177/0363546514542329
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Quantification of Immune-Competent Cells in Baseline Biopsy Specimens From Achilles Tendons

Abstract: New insight into the role of immune-competent cells in chronic Achilles tendinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 58 publications
3
53
0
Order By: Relevance
“…Presence of neovascularization is well documented in advanced tendinopathies and can be demonstrated using Doppler Ultrasound examination [20,22,23,24,25,26]. Similarly, in our study the presence of neovascularization of the LHBT was confirmed in 78% of specimens.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Presence of neovascularization is well documented in advanced tendinopathies and can be demonstrated using Doppler Ultrasound examination [20,22,23,24,25,26]. Similarly, in our study the presence of neovascularization of the LHBT was confirmed in 78% of specimens.…”
Section: Discussionsupporting
confidence: 82%
“…The assessment of neovascularization was based on the criteria from the Bonar scale [18,19,20]. The scores 0, 1, 2, 3 contribute to the following stages of neovascularization seen in ten high-power fields (HPFs): 0 -modest and average occurrence of the blood vessels, 1 -incidental cluster of capillaries less than one per 10 HPFs, 2 -indicates 1-2 clusters per 10 HPFs, 3 -indicates more than 2 clusters per 10 high-power fields.…”
Section: Methodsmentioning
confidence: 99%
“…Interleukin-1ß has been proposed as an initiator of tendinopathy [30] and may be an acceptable model of tendon cell inflammation; however, the issue remains controversial. In any event, persistent presence of macrophages (important sources of IL-1ß) is supported by recent data in patients with chronic tendinopathy who had been followed up for more than 4 years [19]. Ethical issues limit harvesting healthy tendon, and thus we had to use two different anatomical sources for tendon specimen, ie, semitendinosus (healthy tendon) and rotator cuff (tendinopathic tissue).…”
Section: Discussionmentioning
confidence: 92%
“…Growing evidence supports the contribution of inflammation to the development of tendinopathy (16)(17)(18)(19)(20)(21). Whilst animal models of induced tendinopathy have improved our understanding of acute inflammatory processes (22), the phenotypes of the key cells orchestrating inflammation and fibrosis in human soft tissue pathologies such as tendinopathy and enthesopathy have not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%